The bidirectional relationship between AMPK pathway activation and myokine secretion in skeletal muscle: How it affects energy metabolism - Ahsan, Mahdi; Garneau, Léa; Aguer, Céline (Frontiers in Physiology, 2022)
Myokines are peptides and proteins secreted by skeletal muscle cells, into the interstitium, or in the blood. Their regulation may be dependent or independent of muscle contraction to induce a variety of metabolic effects. Numerous myokines have been implicated in influencing energy homeostasis metabolism via AMP-activated protein kinase (AMPK) signalling. As AMPK is centrally involved in glucose and lipid metabolism, it is important to understand how myokines influence its signalling, and vice versa. Such insight will better elucidate the mechanism of metabolic regulation during exercise and at rest. This review encompasses the latest research conducted on the relationship between AMPK signalling and various myokines within skeletal muscles via autocrine or paracrine signalling.